Inter-hemispheric and Intra-hemispheric Transmission of Information on Bimanual and Unimanual Letter Recognition and Matching Tasks - Kumar PJ; Jagadish A (Journal of All India Institute of Speech and Hearing, 1970)
The purpose  of the present  study  was  to  measure  the  time taken  by normal subjects  on bimanual and unimanual letter recognition and matching tasks. 30  subjects  (15 males and 15 females) in  the age range 19-28 years  were considered for  this  study. 13 pairs  of  plastic  letter  cut-out of  English Alphabet  were used. During testing  the subjects  were blind-folded  and  were  asked match  and  recognise  the letters  by feeling. All the subjects were  tested in four different conditions.  It  was found that the sensory information   transmission  from   right   hemisphere  to  left hemisphere  is faster than  from left  hemisphere   to  right.